Osteopontin: An important protein in the formation of kidney stones - Jia, Qingxia; Huang, Ziye; Wang, Guang; Sun, Xia; Wu, Yuyun; Yang, Bowei; Yang, Tongxin; Liu, Jianhe; Li, Pei; Li, Jiongming (Frontiers in Pharmacology, 2022)
The incidence of kidney stones averages 10%, and the recurrence rate of kidney stones is approximately 10% at 1 year, 35% at 5 years, 50% at 10 years, and 75% at 20 years. However, there is currently a lack of good medicines for the prevention and treatment of kidney stones. Osteopontin (OPN) is an important protein in kidney stone formation, but its role is controversial, with some studies suggesting that it inhibits stone formation, while other studies suggest that it can promote stone formation. OPN is a highly phosphorylated protein, and with the deepening of research, there is growing evidence that it promotes stone formation, and the phosphorylated protein is believed to have adhesion effect, promote stone aggregation and nucleation. In addition, OPN is closely related to immune cell infiltration, such as OPN as a pro-inflammatory factor, which can activate mast cells (degranulate to release various inflammatory factors), macrophages (differentiated into M1 macrophages), and T cells (differentiated into T1 cells) etc., and these inflammatory cells play a role in kidney damage and stone formation. In short, OPN mainly exists in the phosphorylated form in kidney stones, plays an important role in the formation of stones, and may be an important target for drug therapy of kidney stones.